Impact of Early Intraocular Pressure Elevation on Postoperative Outcomes After Descemet Membrane Endothelial Keratoplasty in Non-glaucoma Patients. Issue 1 (31st January 2022) - Lentzsch, Anna M.; Adler, Werner; Siebelmann, Sebastian; Grajewski, Rafael; Schrittenlocher, Silvia; Bachmann, Bjoern O.; Cursiefen, Claus; Heindl, Ludwig M.; Matthaei, Mario
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to investigate the impact of transient elevations in postoperative intraocular pressure (IOP) on the clinical outcome of Descemet membrane endothelial keratoplasty (DMEK) surgery in non-glaucoma patients. Methods: Retrospective analysis from a prospective database of eyes without preexisting glaucoma that underwent DMEK with 90% anterior chamber and 20% sulfur hexafluoride endotamponade. Group A included eyes without postoperative IOP increase (IOP <30 mm Hg and a relative increase from preoperative value <10 mm Hg). Group B included eyes with IOP elevation (postoperative IOP ≥30 mm Hg or a relative increase from preoperative value ≥10 mm Hg) handled according to a standardized protocol. The impact of elevated IOP within 3 days after DMEK surgery was evaluated regarding best-corrected visual acuity (BCVA), central corneal thickness (CCT), and endothelial cell count (ECC) at 1, 3, and 6 months. Results: One hundred seventy-six eyes from 164 patients were included. An IOP increase after DMEK occurred in 20 eyes (11.3%; 19 patients, group B), and the mean peak IOP was 48 ± 12 mm Hg (range 32–69 mm Hg). There were no significant postoperative differences in BCVA, CCT, and ECC on comparing both groups. The BCVA increased significantly ( P < 0.001, respectively), whereas CCT ( P < 0.001, respectively) and ECC ( P < 0.001, respectively) decreased significantly from preoperative values. The rebubbling rate tended to be higher in group B without statistical significance (6.4% vs. 10%, P = 0.648). Conclusions: Temporary IOP elevation after DMEK may not affect functional and morphological outcomes in non-glaucoma patients. However, careful postoperative IOP monitoring and appropriate management are crucial to avoid irreversible ocular damage.